Respostas

2013-05-28T15:41:14-03:00

a)5x²-25x=0 (simplifique por 5)

x²-5x=0

x( x-5) = 0

x=0

x-5= 0

x= 5

(raízes 0 e 5)

 

b)5+x²=9

x²=9-5

x²=4

x= (+2 ou -2 raízes)

 

c )7x²-3x=4x+x²

7x²-x²-3x-4x=0

6x²-7x=0

x(6x-7)=0

x=0

6x-7=0

6x=7

x=7/6

(7/6 e 0 raízes)

 

d)z²-8z+12=0

Δ= b²-4ac

Δ= (-8)² -4.1.12

Δ=64-48

Δ=16

 

x= -b +- \sqrt{16} / 2.1

x=-(-8) +- 4/2

x1= (8+4)/2 = 12/2 = 6

x2= (8-4)/2 = 4/2 = 2

(raízes 2 e 6)

 

 

 

1 5 1
  • Usuário do Brainly
2013-05-28T20:46:18-03:00

a) 5\text{x}^2-25\text{x}=0

 

5\text{x}\cdot(\text{x}-5)=0

 

Logo, as raízes são:

 

\text{x}'=0

 

\text{x}''=5

 

 

c) 7\text{x}^2-3\text{x}=4\text{x}+\text{x}^2

 

6\text{x}^2-7\text{x}=0

 

\text{x}\cdot(6\text{x}-7)=0

 

\text{x}'=0

 

\text{x}"=\dfrac{7}{6}

 

 

 

d) \text{z}^2-8\text{z}+12=0

 

\text{z}=\dfrac{-(-8)\pm\sqrt{(-8)^2-4\cdot1\cdot12}}{2\cdot1}=\dfrac{8\pm4}{2}

 

\text{z}'=\dfrac{8+4}{2}=6

 

\text{z}"=\dfrac{8-4}{2}=2